What Firms Want: Investigating Globalization’s Influence on the Market for Lawyers in Korea - Silver, Carole; Lee, Jae-Hyup; Park, Jeeyoon (Columbia Journal of Asian Law, 2014)
This article addresses one of the central debates regarding globalization: how best to approach liberalizing markets in order to balance the interests of local and non-local actors and institutions. It takes the legal services market as its focus and draws on the South Korean (“Korea”) experience as a case study. Korea recently liberalized its regulatory approach to legal services by changing both its method of producing lawyers (including initiating a graduate level law school system and drastically increasing the proportion of bar exam passers) and allowing foreign competition to directly enter its market through foreign law firms and foreign-licensed lawyers working as foreign legal consultants. Arguments for liberalization suggest that competition from foreign actors will introduce benefits to the local market that are particularly important to global actors. In the legal services context, this suggests that global clients may prefer particular expertise and experiences that would be recognized and promoted by the law firms serving them. In our research, we explore this possibility by analyzing the hiring preferences of law firms serving global clients as reflected in the credentials of their lawyers. We draw on a unique dataset comprised of information published by law firms in the form of professional profiles of their lawyers. The firms we analyze are competitors in the global market and include five elite Korean law firms and U.S.-based law firms with Korean-practices situated in their Hong Kong offices—a short airplane trip from Seoul. Our analysis provides insight into the credentials and expertise preferred by each group of firms. From this, we assess the ways in which the two groups of law firms value foreign legal education and law school reputation, as well as the interplay of globalization and gender.